Effect of Dietary Supplementation with Eufortyn® Colesterolo Plus on Serum Lipids, Endothelial Reactivity, Indexes of Non-Alcoholic Fatty Liver Disease and Systemic Inflammation in Healthy Subjects with Polygenic Hypercholesterolemia: The ANEMONE Study - Fogacci, Federica; Rizzoli, Elisabetta; Giovannini, Marina; Bove, Marilisa; D’Addato, Sergio; Borghi, Claudio; Cicero, Arrigo F. G. (Nutrients, 2022)
We aimed to evaluate if dietary supplementation with a nutraceutical compound (Eufortyn® Colesterolo Plus) containing standardized bergamot polyphenolic fraction phytosome (Vazguard®), artichoke extract (Pycrinil®), artichoke dry extract. (Cynara scolymus L.), Q10 phytosome(Ubiqosome®) and zinc, could positively affect serum lipids concentration, systemic inflammation and indexes of non-alcoholic fatty liver disease (NAFLD) in 60 healthy subjects with polygenic hypercholesterolemia. Participants were adhering to a low-fat, low-sodium Mediterranean diet for a month before being randomly allocated to 8-week treatment with 1 pill each day of either Eufortyn® Colesterolo Plus or placebo. Dietary supplementation with Eufortyn® Colesterolo Plus was associated with significant improvement in total cholesterol (TC), low-density lipoprotein cholesterol (LDL-C), non-high-density lipoprotein cholesterol (non-HDL-C), high-sensitivity C-reactive protein (hs-CRP) and endothelial reactivity (ER) in comparison with baseline, and with significant reductions in waist circumference, TC, LDL-C, LDL-C/HDL-C, lipid accumulation product and fatty liver index compared to placebo. The study shows that dietary supplementation with standardized bergamot polyphenolic fraction phytosome, artichoke extracts, Q10 phytosome and zinc safely exerts significant improvements in serum lipids, systemic inflammation, indexes of NAFLD and endothelial reactivity in healthy subjects with moderate hypercholesterolemia.